2014
DOI: 10.1093/annonc/mdu042
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and survival in women with breast cancer—systematic literature review and meta-analysis of 82 follow-up studies

Abstract: The current systematic literature review and meta-analysis extends and confirms the associations of obesity with an unfavourable overall and breast cancer survival in pre and postmenopausal breast cancer, regardless of when BMI is ascertained. Increased risks of mortality in underweight and overweight women and J-shape associations with total mortality were also observed. The recommendation of maintaining a healthy body weight throughout life is important as obesity is a pandemic health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
822
10
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 965 publications
(876 citation statements)
references
References 109 publications
(108 reference statements)
23
822
10
21
Order By: Relevance
“…Recent observations linking obesity (37,39), elevated cholesterol levels (3), low HDL-C (1, 29), and cholesterol metabolites (8) to breast cancer have provided new insights, but the association between HDL-C and mammographic density has been divergent (11,26,27,40). Our findings of an association between HDL-C and mammographic density are supported by others (26), but few studies have reported on the association between hormones and mammographic density stratified by HDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations linking obesity (37,39), elevated cholesterol levels (3), low HDL-C (1, 29), and cholesterol metabolites (8) to breast cancer have provided new insights, but the association between HDL-C and mammographic density has been divergent (11,26,27,40). Our findings of an association between HDL-C and mammographic density are supported by others (26), but few studies have reported on the association between hormones and mammographic density stratified by HDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Unfavorable metabolic profiles, such as high BMI/excess weight and weight gain, are risk factors for postmenopausal breast cancer development (39,49), but the association between excess weight/ weight gain and premenopausal breast cancer may vary by ethnisities and has not yet been clarified (50,51). Thus, different metabolic traits like BMI and HDL during premenopausal years are possible risk factors for postmenopausal breast cancer, and may also be indicators of later breast cancer risk (49) through biomarkers such as mammographic density (11).…”
Section: Discussionmentioning
confidence: 99%
“…Hauner et al came to similar conclusions by assessing examinations and metaanalyses which were published between 1996-2010 [24]. The significance of obesity as a risk factor is increasing with age, especially after menopause [6,25,26], since tumours are characterized by worse response to treatment and great risk of relapse in this period [6,27], whereas women before and after menopause are characterized by worse survival [28]. Similar conclusions were drawn from a meta-analysis of 82 examinations carried out by Chan et al [2014], since worse overall survival among patients with breast cancer is recognized among women with higher BMI (≥30.0 kg/m 2 ).…”
Section: Diet In 2007 World Cancer Research Fund / Americanmentioning
confidence: 82%
“…Similar conclusions were drawn from a meta-analysis of 82 examinations carried out by Chan et al [2014], since worse overall survival among patients with breast cancer is recognized among women with higher BMI (≥30.0 kg/m 2 ). According to the authors' observations, maintaining normal body weigh reduces the risk of breast cancer development, improves prognosis and reduces the possibility of occurrence of oncological treatment complications [28]. It was also shown that patients with normal body weight are less prone to cancer relapse, diabetes and cardiovascular diseases [6].…”
Section: Diet In 2007 World Cancer Research Fund / Americanmentioning
confidence: 99%
“…Authors of the meta-analysis also observed a suggestive association between overweight or obesity and better survival among oesophageal squamous cell carcinoma patients, summarizing evidence from four studies that also showed heterogeneity. A better survival associated with pre-diagnostic overweight or obesity is contrary to what is observed for other obesity-related types of cancer such as breast cancer [30] and colorectal cancer [31]. Although most studies adjusted for tumor stage, residual confounding by clinico-pathological characteristics cannot be excluded.…”
Section: Association Between Obesity and Oesophageal Cancer Survivalmentioning
confidence: 87%